Design and analysis of low power sequence generator module for DNA fragment assembly: article / Nurul Amalina Abu Seman - Abu Seman, Nurul Amalina (2013)
This paper presents the design and analysis of low power Sequence Generator Module (SGM) for DNA Fragment Assembly. The objectives of this project are to construct DNA Fragment Assembly module using Euler algorithm and optimize power consumption of the module. Another objective is to simulate and verify the module in FPGA and ASIC. Power become a primary consideration in design and develops process of a system. DNA fragment assembly system needs a low power consumption since a genome have a large scale of information waiting for decode. Low power techniques were implemented to determine the best approach of standard low power method. The SGM was analyzed using various constraints including clock gating technique to find the lowest power consumption in the module. The design and analysis process successfully done with Xilinx’s software, Verilog Compiler Synopsys(VCS), Design Compiler(DC), Power Compiler(PC) and PrimeTime(PT). The major finding of this analysis is the combination of clock gating technique and power compiler constraints contributed the lowest power consumption in SGM by reducing 98% compared to the analysis of SGM without those techniques. A low power SGM had successfully been developed.